Iatrogenic digestive hemorrhages - Negrotto, Jorge; Niski de Rydel, Rosa (Cirugía del Uruguay, 1974)
Digestive hemorrhages of iatrogenic origin tend to increase, possibly as a consequence of better knowledge of subject and improved techniques. Mechanics of disease varies for the different drugs which are divided, for this purpose, into anti-inflammatory, secretagogues and anti-coagulan•;. Acetyl-salicylic acid is fundamentally a local aggressor, but there are doubts as to whether this action is related with ionization of this substance in mucosa cells or whether, on the contrary, it depends on its absortion speed through gastric epitelium. Corticoids appear to act by modifying quanti and qualitative characteristics of protective mucus. Gastrointestinal alterations conditioning hemorrhageF caused by phenylbutazone are believed to have a general toxic origin acting through the· humoral path. The group of secretagogues act by provoking excessive chlorohydro-peptic secretion and causing, furthermore, vasomotor disturbances. in the gastric submucosa. Anticoagulants may cause digestive hemorrhage due to an excessive dosis or to hypersensibility to the drug, or to a prior gastro-intestinal lesion -latent or known-, by an as yet unknown mechanism (ulcerations induced by anti-vitamin-K drugs). Dosis and latency period vary for eaeh drug, as do precautions which should be faken whenever this type of drug is employed in the prophylaxis of hemorrhages.